Study of online learning for accounting subjects in vocational schools during the pandemic period - Chandra Situmeang; Syahrizal Chalil; Choms G.G.T Sibarani; Dian Y.T.S Situmorang (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
Since COVID-19 pandemic has changed the way people conduct things, including educational activities, online learning has become a necessity that schools must adopt. This study aims to analyze the relationship of various variables that affect the success of online learning in accounting subjects in vocational high. This study is a quantitative cross-sectional online survey with 308 respondents from 26 schools in North Sumatra, Indonesia. Data analysis was performed through regression analysis with moderating variables. It concluded that the success of online learning process as measured by Learning Satisfaction was influenced by Student Characteristics, Learning Accessibility, and Textbooks, while Multimedia Materials and other Text Materials did not have any effect. It further observed that teacher Support does not affect learning satisfaction but can moderate the relationship between student characteristics and textbook quality. This means that all related parties need to focus on changing students' mindset, improving the quality of textbooks, and increasing accessibility. On the other hand, to increase success, it is necessary to strengthen the role of teachers.